PENGUATAN LEMBAGA KONSULTASI PRA-PERCERAIAN SEBAGAI UPAYA PREVENTIF DALAM MENEKAN ANGKA PERCERAIAN DI INDONESIA - Yakub, Moh ibnu yakub (Fakultas Hukum, Universitas Islam Balitar, 2025)
Mediation in household disputes conducted within the court system is often ineffective because it occurs at a stage of high conflict. To strengthen preventive efforts, there is an urgent need to regulate and mandate a pre-divorce consultation stage before filing a lawsuit, considering that currently no specific legal provisions govern this procedure. This study employs a normative method with a descriptive-analytical approach to examine the urgency of such regulation and to analyze its impact on increasing mediation effectiveness. The findings indicate that early mediation through pre-litigation consultation outside the court offers solutions that are more flexible, economical, and participatory. Successful implementation, however, requires adequate legal regulation and inter-agency support. Therefore, this research recommends strengthening the mediation system through the regulation of pre-divorce consultation institutions as the main strategy for the preventive resolution of household disputes in Indonesia.